2010
DOI: 10.1007/s00484-010-0379-0
|View full text |Cite
|
Sign up to set email alerts
|

Perception of temperature and wind by users of public outdoor spaces: relationships with weather parameters and personal characteristics

Abstract: We aim to understand the relationship between people's declared bioclimatic comfort, their personal characteristics (age, origin, clothing, activity and motivation, etc.) and the atmospheric conditions. To attain this goal, questionnaire surveys were made concurrently with weather measurements (air temperature, relative humidity, solar and long-wave radiation and wind speed) in two open leisure areas of Lisbon (Portugal), during the years 2006 and 2007. We analysed the desire expressed by the interviewees to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(90 citation statements)
references
References 35 publications
4
63
1
13
Order By: Relevance
“…The cooler temperatures preferred by the domestic sample in this study can likely be explained by the fact that previous studies have all examined international tourists that are effectively paying to escape cooler conditions to enjoy a warm (hot) holiday (i.e., the survey sample has included tourists traveling from Canada to the Caribbean, or Northern and Central Europe to the Mediterranean), whereas the domestic sample in this study is traveling during the warm summer season to experience similar climatic conditions to their place of origin or perhaps to escape the urban heat by travelling to cooler lake-side conditions. Thermal comfort theory suggests that people adjust their climatic preferences based on expectations, with evidence that the same individual will have differing temperature preferences depending on their expectations of the outdoor conditions [77,78,88]. Tourists leaving temperate regions for tropical holidays are expecting to experience warm/hot conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The cooler temperatures preferred by the domestic sample in this study can likely be explained by the fact that previous studies have all examined international tourists that are effectively paying to escape cooler conditions to enjoy a warm (hot) holiday (i.e., the survey sample has included tourists traveling from Canada to the Caribbean, or Northern and Central Europe to the Mediterranean), whereas the domestic sample in this study is traveling during the warm summer season to experience similar climatic conditions to their place of origin or perhaps to escape the urban heat by travelling to cooler lake-side conditions. Thermal comfort theory suggests that people adjust their climatic preferences based on expectations, with evidence that the same individual will have differing temperature preferences depending on their expectations of the outdoor conditions [77,78,88]. Tourists leaving temperate regions for tropical holidays are expecting to experience warm/hot conditions.…”
Section: Discussionmentioning
confidence: 99%
“…although Lisbon has already been the object of several climatic and bio climatic studies (alcoforado, 1992;andrade, 2003;Lopes, 2003Lopes, , 2006Lopes, and 2009alcoforado and andrade, 2006;alcoforado et al, 2006 and2009a;Vasconcelos and Lopes, 2007;andrade and alcoforado, 2008;andrade et al, 2011), climate information in general, and the climatic comfort in particular, were overlooked in the various instruments of spatial planning, as shown in a systematic analysis of Municipal Plans (PDM), p erformed by alcoforado and Vieira (2004). However, some results of the work of alco forado et al (2005) have been included as Climatic Guidelines within the revi sed PDM of Lisbon.…”
Section: Introductionmentioning
confidence: 99%
“…this cooling effect can extend to the surrounding areas, depending on the urban geometry, the characteristics of the green area and the general weather conditions (Cohen et al, 2012;Hamada et al, 2013). Oliveira et al (2011) found that on particularly hot days in Lisbon, the differences in temperature between Ga-a (cooler) and other spots located up to 300 m south of the park were significant, varying as a function of sun exposure, street orientation and wind speed. the lower differences between the various locations in the nearest surroundings of Ga-a, in relation to Ga-B, can be due to the urban geometry and consequent sun expo sure, as green area a is smaller and it is surrounded by tall buildings on all sides increasing the number of hours of shade that affected the thermo-hygrometers outside the green area.…”
Section: Weather Conditions Of the Green Areas And Their Surroundingsmentioning
confidence: 99%
“…Green areas can also have an important role in climate change adaptation; the expected global changes may accumulate with the urban thermal e ffects, increasing the vulne rability of urban areas to the impacts of climate change (Patz et al, 2005;Wilby and Perry, 2006;alcoforado and andrade, 2008). in this context, the microclimatic influen ce of green areas in the surrounding areas, particularly the cooling effect in hotter seasons (Lafortezza et al, 2009;Zoulia et al, 2009;Oliveira et al, 2011;Cohen et al, 2012), can mitigate the effects of the esti mated increase in temperatures and heat waves, whose frequency and intensity are expected to rise (santos and Miran da, 2006;Parry, 2007;alcoforado and a ndrade, 2008); moreover, urban vege tation, particularly trees, also contribute to CO 2 uptake (akbari, 2002). additionally, green areas play an important role in recreation, providing noise protection and facilities to their users (Haq, 2011), either locals or tourists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation